Synthesis of germanium nanocrystals from solid-state disproportionation of a chloride-derived germania glass. Issue 43 (9th May 2019) - Wang, Yujie; Ramesh, Utkarsh; Nyamekye, Charles K. A.; Ryan, Bradley J.; Nelson, Rainie D.; Alebri, Abdulla M.; Hamdeh, Umar H.; Hadi, Atefe; Smith, Emily A.; Panthani, Matthew G.
Abstract : Germanium nanocrystals (Ge NCs) have potential to be used in several optoelectronic applications such as photodetectors and light-emitting diodes. Abstract : Germanium nanocrystals (Ge NCs) have potential to be used in several optoelectronic applications such as photodetectors and light-emitting diodes. Here, we report a solid-state route to synthesizing Ge NCs through thermal disproportionation of a germania (GeO X ) glass, which was synthesized by hydrolyzing a GeCl2 ·dioxane complex. The GeO X glass synthesized in this manner was found to have residual Cl content. The process of nanocrystal nucleation and growth was monitored using powder X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy and Raman spectroscopy. Compared to existing solid-state routes for synthesizing colloidal Ge NCs, this approach requires fewer steps and is amenable to scaling to large-scale reactions.